Clinical Outcomes of a Genomic Screening Program for Actionable Genetic Conditions. Issue 4 (April 2021) - Buchanan, Adam H.; Kirchner, H. Lester; Schwartz, Marci L. B.; Kelly, Melissa A.; Schmidlen, Tara; Jones, Laney K.; Hallquist, Miranda L. G.; Rocha, Heather; Betts, Megan; Schwiter, Rachel; Butry, Loren; Lazzeri, Amanda L.; et al.
Abstract : (Abstracted from Genet Med 2020;22:1874–1882) Hereditary breast and ovarian cancer (HBOC), Lynch syndrome, and familial hypercholesterolemia (FH) are recognized by the Centers of Disease Control and Prevention as tier-1 genetic conditions for which early identification and management could decrease morbidity and mortality. Yet few patients with a personal or familial history of these conditions are screened for genetic risk.